The Determinants of Teacher Supply - Zabalza, A. (Review of Economic Studies, 1979)
Journal Article The Determinants of Teacher Supply Get access A. Zabalza A. Zabalza London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 131–147, https://doi.org/10.2307/2297177 Published: 01 January 1979 Article history Received: 01 April 1977 Accepted: 01 February 1978 Published: 01 January 1979